Prevalence and Socio-Demographic Determinant of Overweight and Obesity among Malaysian Adult - Ahmad Ali Zainuddin,; Mala A Manickam,; Azli Baharudin,; Rusidah Selamat,; Kee, Chee Cheong; Noor Ani Ahmad,; Hatta Mutalip,; Rashidah Ambak,; Cheong, Siew Man; Mohamad Hasnan Ahmad,; Safiah Md Yusof,; Tahir Aris, (Universiti Kebangsaan Malaysia, 2016)
Introduction: Overweight and obesity is a major public health problem in Malaysia. This study aims to determine the prevalence of overweight and obesity among the Malaysian adult population and their association with socio-demographic characteristics (gender, ethnic, and age groups). Methods: A total of 17,257 adults aged 18 years and older (8,252 men, 9,005 women) were assessed for BMI status, with a response rate of 97.8%, through a household survey from the National Health and Morbidity Survey (NHMS), conducted in all states of Malaysia in 2011. Results: All socio-demographic factors were consistently associated with higher chance of being overweight (except gender and location) and obesity (except location and household income). The identified risk of overweight were Indian (aOR: 1.8, 95% CI: 1.2-2.8), aged 50-59 years (aOR: 2.8, 95% CI: 2.0-3.9), widower (aOR: 1.6, 95% CI: 1.3-2.0), subject with secondary education (aOR: 1.2, 95% CI: 1.0-1.4), Homemaker/unpaid worker (aOR: 1.3, 95% CI: 1.1-1.4), and with high household income group (aOR: 1.3, 95% CI: 1.2-1.6). The identified risk of obesity were women (aOR: 1.4, 95% CI: 1.2-1.6), Indian (aOR: 1.7, 95% CI: 0.9-3.2), aged 30-39 years (aOR: 3.6, 95% CI: 2.4-5.5), widower (aOR: 1.2, 95% CI: 0.9-1.6), subjects with primary education (aOR: 1.2, 95% CI: 0.9-1.6), Homemaker/unpaid worker(aOR: 1.3, 95% CI: 1.1-1.6), and with middle household income group (aOR: 1.3, 95% CI: 1.2-1.6). Conclusions: Our data indicate a high prevalence of overweight and obesity in the population. Several sociodemographic characteristics are associated with both overweight and obesity. This study highlights the serious problem of overweight and obesity among Malaysia adults. Documentation of these problems may lead to research and policy agendas that will contribute both to our understanding and to the reduction of these problems.